PENGARUH MODEL INKUIRI TERHADAP HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Wipa Arifia Hidayah; Riri Marfilinda; Sisri Wahyuni (LP2M Universitas Adzkia, 2025)
This study aimed to determine the effect of the inquiry learning model on elementary school students’ science learning outcomes. The study was motivated by the low science learning outcomes and the limited use of learning models that actively involve students in the learning process. The research employed a quasi-experimental design using the nonequivalent posttest-only control group design. The study was conducted in the 2025/2026 academic year involving two classes: an experimental class taught using the inquiry learning model and a control class taught using conventional learning. The sampling technique used saturated sampling, in which all members of the population were selected as the research sample. Data were collected through a posttest consisting of 20 objective questions that had been tested for validity, reliability, discrimination index, and difficulty level. The results showed that the average posttest score of the experimental class was higher than that of the control class, namely 94 and 80. The Mann-Whitney U test result obtained an Asymp. Sig. (2-tailed) value of 0.011 < 0.05, indicating that H₀ was rejected and H₁ was accepted. Therefore, the inquiry learning model had a significant effect on students’ science learning outcomes.